A CRIANÇA COM DEFICIÊNCIA INTELECTUAL E O DESENVOLVIMENTO DAS FUNÇÕES PSICOLÓGICAS SUPERIORES: UM OLHAR PARA AS PRÁTICAS PEDAGÓGICAS - Braga, Livia Vares da Silveira (2020)
This study aimed to investigate how pedagogical practices can contribute to the development of higher psychological functions of children with intellectual disabilities in early childhood education. As specific goals, we sought to analyze the role of medi